Prevalence of musculoskeletal disorders among blacksmith workers in Sawan Village Sawan District Buleleng Regency Bali - Gde Bagus Raditya Nugraha Nukarna; Ni Luh Putu Ariastuti; Komang Ayu Kartika Sari (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Blacksmithing work poses high risks for occupational diseases, including musculoskeletal disorders (MSDs), such as hearing loss, injuries from sharp tools, and muscle strain from hammering activities. In Sawan Village, there are 25 workplaces with at least two workers per location, most of whom report fatigue and discomfort. Purpose: To describe the prevalence of musculoskeletal disorders among blacksmith workers in the village. Method: A descriptive study design with a cross-sectional method and total sampling technique, involving 50 workers from 25 blacksmithing centers. Data were collected using risk factor questionnaires, Nordic Body Map (NBM) questionnaires, and measurements of body weight and height. Data analysis was conducted through cross-tabulation using SPSS software, based on risk factors and the severity of the disorders. Results: Showed that most workers were under 45 years old (75%), had a BMI classified as thin-normal (72.72%), had 11-20 years of experience (59.09%), worked ≤8 hours per day (54.55%), and took breaks lasting less than 60 minutes (43.18%). Musculoskeletal disorders were predominantly found in the wrists and hands, with all respondents (100%) categorized as having a low-risk level. Conclusion: 44 workers reported musculoskeletal complaints, all within the low-risk category. Suggestion: Interventions in the form of improving work ergonomics, regulating rest periods, and occupational health education are essential to reduce the risk of MSDs and improve the quality of work of blacksmiths.